2004
DOI: 10.1128/jb.186.17.5741-5752.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Diversity and Molecular Evolution of the Heat-Modifiable Outer Membrane Protein Gene ( ompA ) of Mannheimia ( Pasteurella ) haemolytica , Mannheimia glucosida , and Pasteurella trehalosi

Abstract: The OmpA (or heat-modifiable) protein is a major structural component of the outer membranes of gramnegative bacteria. The protein contains eight membrane-traversing ␤-strands and four surface-exposed loops. The genetic diversity and molecular evolution of OmpA were investigated in 31 Mannheimia (Pasteurella) haemolytica, 6 Mannheimia glucosida, and 4 Pasteurella trehalosi strains by comparative nucleotide sequence analysis. The OmpA proteins of M. haemolytica and M. glucosida contain four hypervariable domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
63
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 58 publications
(62 reference statements)
0
63
0
1
Order By: Relevance
“…Transfer of X. nematophila nilABC genes into two species of Xenorhabdus that did not colonize S. carpocapsae (X. poinarii and X. bovienii) enabled these species to symbiotically colonize S. carposapsae [18]. Similarly, in the Gram-negative bacteria, protein OmpA constitutes the outer membranes [26]. OmpA has many functions, including adherence to host tissues in several pathogenic bacteria (summarized in [26]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transfer of X. nematophila nilABC genes into two species of Xenorhabdus that did not colonize S. carpocapsae (X. poinarii and X. bovienii) enabled these species to symbiotically colonize S. carposapsae [18]. Similarly, in the Gram-negative bacteria, protein OmpA constitutes the outer membranes [26]. OmpA has many functions, including adherence to host tissues in several pathogenic bacteria (summarized in [26]).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the Gram-negative bacteria, protein OmpA constitutes the outer membranes [26]. OmpA has many functions, including adherence to host tissues in several pathogenic bacteria (summarized in [26]). Difference in OmpA hypervariable domains has been linked to host specificity between cattle and sheep isolates of Mannheimia (Pasteurella) haemolytica, M. glucosida, and P. trehalosi [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adherence of respiratory pathogens to the mucosal epithelium is critical in host colonization and infection (Beachey 1981). Based on sequence homology, Davies and Lee (2004) suggested that the OmpA of M haemolytica is involved in binding to bovine and ovine receptors, thus playing an important role in the colonization of the respiratory tracts of cattle and sheep. It has also been demonstrated that OmpA shows a specific interaction with the extracellular matrix (EMC) protein fibroncctin (Lo and Sorenscn 2007) and that it contributes to adher ence of M. haemolytica to bovine bronchial epithelial cells (BBEC) in vitro (Kisiela and Czuprynski 2009).…”
mentioning
confidence: 99%
“…It has been shown that the majority of polymorphic nucleotide sites in the ompA gene of M haemolytica occurs in four hypcrvariablc domains within the surface-exposed loops (Davies and Lee 2004).…”
mentioning
confidence: 99%